Sickle cell disease is a global prototype for integrative research and healthcare. Issue 1 (25th February 2021) - Royal, Charmaine D. M.; Babyak, Michael; Shah, Nirmish; Srivatsa, Shantanu; Stewart, Kearsley A.; Tanabe, Paula; Wonkam, Ambroise; Asnani, Monika
Abstract: Differences in health outcomes and treatment responses within and between global populations have been well documented. There is growing recognition of the need to move beyond simple inventories and descriptions of these differences and our linear explanations for them, and gain a better understanding of the multifaceted systems and networks underlying them in order to develop more precise and effective remedies. Typical targets for such integrative research have been common multifactorial diseases. We propose sickle cell disease, one of the most common monogenic diseases, as an ideal candidate for elucidating the complexity of the influences of endogenous and exogenous factors on disease pathophysiology, phenotypic diversity, and variations in responses to treatments at both the individual and population levels. We provide data‐informed representations of diverse contributors to sickle cell disease complications that could guide innovative efforts to advance scientific knowledge, clinical practice, and policy formulation related to the disease; help improve outcomes for people worldwide with sickle cell disease; and inform approaches to studying and addressing other diseases. Abstract : Sickle cell disease, one of the most common monogenic diseases with global reach, illustrates the complexity of the influences of endogenous and exogenous factors on disease pathophysiology, phenotypic diversity, and variations in responses to treatments. Multiple domains of influence comprise intricate networks that interact with one another over the life course at both the individual and population levels. These biological, psychological, clinical, behavioral, sociocultural, structural, and environmental variables interact to produce episodes of clinical disease and changing experience of disability and resilience. Data from both clinical records and affected individuals suggest conceptual models that can in turn be tested statistically. Other monogenic disorders could also serve to model and decode more common and etiologically complicated health conditions, advancing global efforts to improve and sustain health.